Democratic Leadership Style, Excessive Working Hours, Organizational Citizenship Behavior on Employee Performance - Fahri Kusumapuri; Ryani Dhyan Parashakti (DEAL: International Journal of Economics and Business, 2024)
This research aims to analyze the relationship between democratic leadership style, excessive working hours, and organizational citizenship behavior (OCB) on employee performance in the organizational area. A democratic leadership style is known because it provides opportunities for employees to participate in decision making, whereas excessive working hours can have an impact on balancing work and individual employee lives. OCB includes voluntary behavior that goes beyond the demands of official duties, such as helping coworkers or contributing to revisions to work processes. It is hoped that the results of this research will provide knowledge about how democratic leadership style, excessive working hours, and OCB can influence employee performance. These findings can help organizational management in designing more efficient leadership strategies, establishing balanced working hours policies, and encouraging positive organizational citizenship attitudes to improve overall employee performance.